2020
DOI: 10.1149/1945-7111/ab68c8
|View full text |Cite
|
Sign up to set email alerts
|

Transient Gas Distribution in Porous Transport Layers of Polymer Electrolyte Membrane Electrolyzers

Abstract: Here, we elucidated the dynamic gas transport behavior in the anode porous transport layer (PTL) of polymer electrolyte membrane (PEM) electrolyzers via in operando synchrotron X-ray imaging. The imaging results showed that the gas saturation in the PTL reached steady state more rapidly with a steep current density ramp-up and a shallow ramp-down (compared to a shallow ramp-up and a steep ramp-down, respectively). Additionally, the gas accumulation was characterized by a faster response time compared to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…When the gas pressure is further increased after breakthrough of the gas phase, a water-gas barrier is formed in the 3D pore networks. The striking differences between the two simulations are the final saturations with liquid and gas phases at breakthrough, as well as the invasion behavior after breakthrough, if it is assumed that the gas phase can be forced to further invade the porous structure by increasing the gas pressure, e.g., provoked by the very low gas permeability in the studied case of laminar, incompressible gas flow (Figure 10) or based on diffusion resistances [49]. The pore network simulations indicate that the gas saturation at the top side can be reduced from around 50% to around 30% by application of a pore size gradient (Figure 9).…”
Section: Drainage Simulationmentioning
confidence: 98%
See 1 more Smart Citation
“…When the gas pressure is further increased after breakthrough of the gas phase, a water-gas barrier is formed in the 3D pore networks. The striking differences between the two simulations are the final saturations with liquid and gas phases at breakthrough, as well as the invasion behavior after breakthrough, if it is assumed that the gas phase can be forced to further invade the porous structure by increasing the gas pressure, e.g., provoked by the very low gas permeability in the studied case of laminar, incompressible gas flow (Figure 10) or based on diffusion resistances [49]. The pore network simulations indicate that the gas saturation at the top side can be reduced from around 50% to around 30% by application of a pore size gradient (Figure 9).…”
Section: Drainage Simulationmentioning
confidence: 98%
“…Apart from the optimization of mass transfer properties, the change of the ohmic resistances for charge transfer must also be considered to achieve the optimal structural design [35]. Experimental studies in the literature indicate that the realization of the connectivity of the PTL with the catalyst layer and the degradation of material properties play major roles in performance enhancement [35,49,55], while other studies reveal the impacts of temperature and pressure [47].…”
mentioning
confidence: 99%
“…Their observations surprising at a time, suggested that the PTL would always be saturated with water, regardless of the current density and that oxygen saturation did not change with current density in the regime of 0.1 -2.5 A/cm 2 . Lee et al (C. Lee et al, 2020) have investigated the dynamic gas transport behavior in the anode PTL by using operando synchrotron x-ray imaging. When they applied the current with a steep ramp-up and a shallow ramp-down.…”
Section: Introductionmentioning
confidence: 99%
“…As an effort to better understand the two-phase transport behavior in the PTL, studies ( Abdin et al., 2015 ; Dedigama et al., 2014 ; García-Valverde et al., 2012 ; Han et al., 2016 ; Kadyk et al., 2016 ; Kang et al., 2018 ; 2017 ; Kim et al., 2020 ; Lee et al., 2020a ; Lee et al., 2017 ; Leonard et al., 2020 ; 2018 ; Lopata et al., 2020 ; Schuler et al., 2019 ; Seweryn et al., 2016 ; Suermann et al., 2017 ; Zlobinski et al., 2020 ) have focused on using imaging techniques to investigate the evolution and transport of oxygen in electrolyzers, including optical, neutron, or X-ray imaging, as well as computational studies. Optical microscopy was utilized by Dedigama et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al. ( Lee et al., 2020a ) have investigated the dynamic gas transport behavior in the anode PTL by using operando synchrotron X-ray imaging. When they applied the current with a steep ramp-up and a shallow ramp-down, they concluded that the oxygen responds more rapidly, which means that the gas saturation in the PTL reached a steady state quickly.…”
Section: Introductionmentioning
confidence: 99%